Strategies identified by program directors to improve adoption of the CanMEDS framework - Gaboury, Isabelle; Ouellet, Kathleen; Xhignesse, Marianne; St-Onge, Christina (Canadian Medical Education Journal, 2018)
Background: Challenges associated with the use of the CanMEDS physician competency framework (CanMEDS) have been the subject of several studies. Most of these have focused on the adoption of specific roles in an Anglophone context. This study aims to investigate how Francophone postgraduate medical education (PGME) program directors have integrated the CanMEDS framework into their programs. Methods: We invited Francophone PGME program directors to participate in group interviews aimed at exploring their experiences using the CanMEDS framework. We used an open-ended interview guide and realized a thematic analysis of the transcripts. Results: We held five group interviews between February and December 2014 with 17 Francophone program directors representing 13 out of a maximum of 62 different specialties/subspecialties. Although program directors endorsed the framework, its integration was seen as challenging, particularly the assessment of non-medical expert roles. To overcome these challenges, they relied on common strategies including a longitudinal approach to the framework, improving inter-program collaboration, and subcontracting the teaching of certain roles. Conclusion: While integrating the CanMEDS framework into their programs, Francophone program directors struggled with teaching and assessing non-medical expert roles and ensuring their longitudinal integration over time. Directors relied on various strategies, some of which (e.g., subcontracting) may ultimately limit the adoption of the framework as a whole. ___ Contexte: Les défis associés à l'utilisation du référentiel de compétences CanMEDS pour les médecins ont fait l'objet de plusieurs études. La plupart de ces études ont portées sur l'adoption de rôles spécifiques dans un contexte anglophone. Cette étude vise à explorer comment les directeurs de programmes d’études médicales postdoctorales (EMP) francophones ont intégré CanMEDS dans leurs programmes. Méthodes: Nous avons invité les directeurs de programmes EMP francophones à participer à des entrevues de groupe. Ces entrevues visaient à explorer leur expérience de l’utilisation du référentiel CanMEDS. Nous avons utilisé un guide d'entrevue ouvert et nous avons fait une analyse thématique des transcriptions. Résultats: Nous avons tenu cinq entrevues de groupe entre février et décembre 2014 avec 17 directeurs de programmes de 13 des 62 spécialités/sous-spécialités. Bien que les directeurs de programmes appuient le référentiel, son intégration a été perçue comme un défi, notamment en ce qui a trait à l'évaluation des rôles autres que celui d'expert médical. Pour surmonter ces défis, ils se sont appuyés sur des stratégies communes, notamment une approche longitudinale du référentiel, l'amélioration de la collaboration entre les programmes et la sous-traitance de l'enseignement de certains rôles. Conclusions: À travers le processus d’intégration du référentiel CanMEDS, les directeurs de programmes EMP francophones ont de la difficulté à enseigner et à évaluer les rôles autres que celui d'expert médical ainsi qu’à veiller à leur intégration respective et continue au fil du temps. Ils ont eu recours à diverses stratégies, dont certaines (p. ex., la sous-traitance) pourraient ultimement limiter l'adoption du référentiel dans son ensemble.